A dream of ebony and white eaudiobook A retelling of snow white. - Melanie Cellier (Beyond the Four Kingdoms, 2019)
Snow has always lived under the shadow of her cruel stepmother, with only her beloved father and her childhood friend—the huntsman, Alexander—to make life bearable. When her father dies, she should be crowned queen, but instead she finds herself fleeing for her life. With no allies, no skills, and no food, her future could be over before it has truly begun. But there's more at stake than just one life. If Snow can't claim her throne, her kingdom faces destruction. Snow has to make a choice: focus on her own salvation or put everything on the line—even those she loves the most. And if she's going to succeed, Snow must fight the hardest battle of all, against her own doubt and weakness, and gain new skills and strength she never imagined possessing. Alexander is ready to help her. But if she lets him, the consequences might be more than she can bear—because her heart is in as much jeopardy as the kingdom. In this reimagining of the classic fairy tale, Snow must find her inner strength in time to fight for her throne before it's too late.